PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS TERHADAP KEMAMPUAN BERBICARA SISWA KELAS V SD NEGERI 120 BERRU KABUPATEN SOPPENG - herman, nabila; Rukayah; Abd. Kadir (MACCA : Science-Edu Journal, 2025)
This research aims to determine the difference in the speaking ability of fifth grade students of SD Negeri 120 Berru Soppeng Regency before and after the application of the Cooperative Learning model type Talking Chips by using quantitative approach. The research design used is One group Prestest-Posttest design. The variables in this study are the Talking Chips model as the independent variable and the dependent variable which is speaking ability, with the number of research subjects as many as 28 students. The data collection technique used was a 2-time test to determine the students' speaking ability before and after applying the Talking Chips Cooperative Learning Model. Data analysis using descriptive statistical analysis and inferential statistical analysis.The results showed that before the application of Talking Chips model, the pretest scores obtained by students were with an average of 54.18 and after applying the Talking Chips Cooperative Learning model, the students' posttest results experienced an average 80.18. The conclusion of this research is that there is difference between before and after application of model of Cooperative Learning Type Talking Chips in the speaking ability of fifth grade students of SD Negeri 120 Berru Soppeng Regency.